Erythromelalgia? A Clinical Study of People Who Experience Red, Hot, Painful Feet in the Community. (15th May 2013) - Friberg, D.; Chen, T.; Tarr, G.; van Rij, A.
Abstract : We recruited a population of people who clinically suffer from the symptoms of erythromelalgia, red, hot, painful feet made worse by heat and improved by cooling, to better characterise this population and measure their quality of life (QOL). Ninety-two individuals completed the QOL surveys, and 56 individuals were clinically assessed. There was a 3 : 1 ratio of females to males with an average age of 61 years. The estimated prevalence of people who had clinical symptoms of erythromelalgia in the Dunedin community was 15/100, 000. Only 27% of people had received a diagnosis for their symptoms despite seeking medical attention. People in the study population had worse quality of life than the general New Zealand population( P < 0.001 ) . In the majority of participants symptoms had a mild-moderate effect on their quality of life. The results of this study indicate that the number of people who have clinical symptoms of erythromelalgia is much greater than is commonly accepted and that the majority of these individuals go unrecognised by the medical profession despite seeking help. They have significantly diminished QOL with the majority of people having mild-to-moderate symptoms.